Optimizing the coupled effects of Hall-Petch and precipitation strengthening in a Al0.3CoCrFeNi high entropy alloy. (5th May 2017) - Gwalani, B.; Soni, Vishal; Lee, Michael; Mantri, SA; Ren, Yang; Banerjee, R.
Abstract: A successful demonstration of applying integrated strengthening using Hall-Petch strengthening (grains size effect) and precipitation strengthening is shown in the fcc based high entropy alloy (HEA) Al0.3 CoCrFeNi, leading to quantitative determinations of the Hall-Petch coefficients for both hardness and tensile yield strength, as well as the enhancements in the yield strength from two distinct types of ordered precipitates, L12 and B2. An excellent combination of yield strength (~ 490 MPa), ultimate tensile strength (~ 850 MPa), and ductility (~ 45% elongation) was achieved by optimizing and coupling both strengthening mechanisms, resulting from a refined grain size as well as both L12 and B2 ordered precipitates. This opens up new avenues for the future development of HEAs, with the appropriate balance of properties required for engineering applications. Graphical abstract: Highlights: Fcc based Al0.3 CoCrFeNi HEA shows very high propensity to grain-boundary strengthening (Hall-Petch effect) Al0.3 CoCrFeNi can be further precipitation strengthened by two different types of ordered (L12 & B2) precipitates Coupling Hall-Petch strengthening with precipitation strengthening via both L12 & B2 precipitates results in excellent strength-ductility combination